HUBUNGAN MINAT BACA DAN LINGKUNGAN BELAJAR DI SEKOLAH DENGAN PRESTASI BELAJAR - Eva Ristiani; Erlina Rupaidah; Darwin Bangun (FKIP Unila, 2014)
This study aims to determine the relationship of interest in reading and learning environment at school on integrated social studies achievement in class VIII of SMP Muhammadiyah 1 Wonosobo academic year 2013/2014. The method used descriptive associative with an ex post facto approach and surveys. Sampling is a probability sampling using the formula of T. Yamane. In order to test hypothesis, it uses product moment correlation and multiple. Based on the analysis of the data, it obtained: (1) There is a relationship between interest in reading and integrated social studies achievement; (2) There is a relationship between learning environment in school and integrated social studies achievement; (3) There is a relationship between interest in reading and learning environment in school on integrated social studies achievement.Penelitian bertujuan mengetahui hubungan minat baca dan lingkungan belajar di sekolah dengan prestasi belajar IPS Terpadu siswa kelas VIII SMP Muhammadiyah 1 Wonosobo Tahun Pelajaran 2013/2014. Metode penelitian menggunakan deskriptif asosiatif dengan pendekatan ex post facto dan survei. Teknik sampling probability sampling menggunakan rumus T. Yamane. Untuk menguji hipotesis, menggunakan korelasi product moment dan multiple. Berdasarkan analisis data diperoleh: (1) Ada hubungan minat baca dengan prestasi belajar; (2) Ada hubungan lingkungan belajar di sekolah dengan prestasi belajar; (3) Ada hubungan minat baca dan lingkungan belajar di sekolah dengan prestasi belajar.Kata kunci: lingkungan belajar, minat baca, prestasi belajar